Reconnection heating experiments and simulations for torus plasma merging start-up. (7th June 2019) - Ono, Y.; Inoue, S.; Tanabe, H.; Cheng, C.Z.; Hara, H.; Horiuchi, R.
Abstract: A series of merging experiments, TS-3 (TS-3U), TS-4, MAST and ST-40, made clear the promising characteristics of reconnection heating during merging formation of a high-beta spherical tokamak (ST), spheromak and field-reversed configuration (FRC). We developed the MW-class (<30 MW in TS-3U) ion heating using magnetic reconnection of torus plasma merging. Both the merging experiments and particle-in-cell (PIC) simulations (and also partly solar observation) agree on, (i) ion heating of the reconnection in its downstream, (ii) negative potential formation in the downstream for accelerating ions and (iii) low dependence of ion heating on the guide (toroidal) field B g . An important finding is that the reconnection heating energy depends on the reconnecting magnetic field B rec but has little dependence on B g in the tokamak operation region with the safety factor at the magnetic axis q 0 > 2. The plasmoid/current sheet ejection promotes ion heating in the high- q region, weakening the B g dependence of ion heating. Since the reconnection accelerated ions up to 70% of the Alfven speed of B rec, the ion temperature T i increment (and the reconnection heating energy) scales with B rec squared under the constant plasma density. This promising reconnection heating does not depend on plasma size, as long as the reconnection time is shorter than the plasma confinement time. This scaling law extended over 1.2 keV suggests that the merging start-up may realize the burning plasma temperature T i > 10 keV by increasing B rec . The merging/reconnection heating can explore a new direct route to burning plasma regimes without using any additional heating, such as neutral beam injection (NBI). This scaling leads us to new reconnection heating experiments for direct access to burning plasma regimes: ST-40 at Tokamak Energy and TS-3U at the University of Tokyo.